Applying the Foresight Approach as an Analytic Tool in Non-Traditional Security: Case Study of Environmental Security - Tran, Ca Ngoc; Trinh, Quyen Van; Hoang, Huong Thanh (Journal of disaster research, 2025)
Environmental issues and security are critical to contemporary international development. As a component of nontraditional security, environmental security plays a vital role in fostering stability, prosperity, and sustainability for the future of a nation. Strategic planning and long-term policy formulation to address environmental challenges are integral to a country’s capacity for development. However, traditional methodologies and frameworks may be insufficient for effectively managing the risks and threats associated with nontraditional security. This study examines the interconnections between non-traditional security, particularly environmental security, and long-term strategic planning, while exploring the potential of alternative approaches to shape the future. Among these, the foresight approach has emerged as a promising tool for addressing the existing limitations. Techniques, such as scenario building and the Delphi method, are among the most widely used in future studies. Past experience with the application of foresight in Vietnam and other contexts may provide insights into its practical relevance. Furthermore, within the broader framework of nontraditional security, foresight has the potential to contribute to a safer and more resilient future by mitigating or preventing emerging risks and threats. Its strengths, including participatory planning and the dynamic nature of scenarios, should be explored further in the context of environmental strategy development and policymaking. A more rigorous and proactive application of foresight is recommended to address the security concerns regarding environmental policies and strategic planning processes.